Role and Challenges of Ngos In Empowering Women in Rural Areas of Balochistan, Pakistan (Journal of Governance and Development (JGD), 2016)
Empowerment of women is essential and prerequisite for sustainable rural development of Balochistan. NGO’s play a very pivotal role in empowering them by providing basic education, vocational training for self-employment, legal aid, protection for women and self-awareness programme. However, NGOs working in these areas face socio-cultural challenges. The purpose of this paper is to explore the role and challenges of the NGOs in empowering women in rural areas of Balochistan. The data were obtained through the interview schedule using snowball sampling method. 20 informants interviewed. The results show the NGOs are playing an important role in empowering women in different fields in a challengeable socio-cultural environment, due to the socio cultural barriers, few NGOs were active. Two NGOs were selected for study who were engaged in different projects of women empowerment. This paper is intended to be a valuable contribution in highlighting the efforts of NGOs in a dominating cultural setup.